Water Quality Study at Educational Area in Bandar Seri Alam, Johor, Malaysia - Farid Muhammad Fathullah, Muhammad; Zafyrah Mohd Zahid, Azyan; Farahin Kamaruddin, Siti; Zulkhairi Mat Salleh, Mohd; Syarizawani Wan Chik, Wan; Khalid, Noorashiekin; Mat Zin, Mazni; Zalikha Saifullizam, Nadia; Ain Umaiban Yusof, Nurul; Firdaus Mohd Akhbar, Mohd (International Journal of Engineering and Technology, 2018)
This research study is conducted to provide water quality data of detention pond at UiTM Pasir Gudang Campus (UiTMCJKPG) and to ascertain the suitability of this newly potential water supply source for gardening and landscaping activities in this campus. According to Department of Environment (DoE) Malaysia, 6 water quality parameters must be tested in order to recognize the suitability of the water quality status. These parameters are categorized into physical, chemical and biological characteristics. Based on the intended usage of this new source, the detention pond is classified under Class IIB. As such, the limit for the selected parameters is restricted under this category and must not be exceeded. 16 sampling points have been identified covering along the circumference of detention pond and the inflow point. Several water quality tests such as temperature, pH, turbidity and dissolved oxygen measurement are conducted in-situ while other parameters which mainly subjected to chemical and biological testing are determined in laboratory. The outcome of this research shows that the water quality of retention pond in UiTM Pasir Gudang (UiTMCJKPG) complied with the standard requirement of Class IIB thus making it as an accepted new source of water supply for gardening and landscaping maintenance activities.Â Â